1998
DOI: 10.1006/mssp.1997.0138
|View full text |Cite
|
Sign up to set email alerts
|

On Model Updating Using Neural Networks

Abstract: Key parameters in dynamic systems often change during their life cycle due to repair and replacement of parts or environmental changes. This paper presents a new approach to account for these changes by updating the system models. Current iterative methods developed to solve the model updating problem rely on minimisation techniques to find the set of model parameters that yield the best match between experimental and analytical responses. These minimisation procedures require considerable computation time, ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…The generated samples should re#ect the probability distribution of the parameters to be considered. Atalla and Inman [4] reported that a random generation of samples yields the best result for the NN training.…”
Section: Other Selection Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The generated samples should re#ect the probability distribution of the parameters to be considered. Atalla and Inman [4] reported that a random generation of samples yields the best result for the NN training.…”
Section: Other Selection Methodsmentioning
confidence: 99%
“…They are the full factorial (FF), the hypercube (HC) [22], the linear (LI) [16], and the random (RA) method [4,16].…”
Section: Other Selection Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To avoid large neural networks, one can use a subset of the available FRF data by considering fewer measurement points and by de"ning frequency windows. Atalla and Inman [6] updated a 15-DOF lumped-parameter system and a #exible frame structure using an RBF neural network, the input to which consisted of pre-selected frequency points from a number of frequency windows. An alternative approach, based on modal parameter input, is described by Levin and Lieven [7].…”
Section: Introductionmentioning
confidence: 99%